2021
DOI: 10.1186/s12889-021-11752-2
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity by school socioeconomic composition and adolescent socioeconomic status: a school-based study

Abstract: Background The main objective of this study was to investigate the interaction effect of school socioeconomic composition (SEC) and adolescent socioeconomic status (SES) in the prevalence of overweight and obesity among a representative sample of French adolescents of the third most populous département of France. Methods 1038 adolescents agreed to participate (response rate: 91.4%). They self-reported anthropomorphic variables, SES, school lunch a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The interaction effect also can be found in the developed country and developing country, Low SES is risk factor for obesity in the developed country but is protective factor in developing country [8]. The studies above have proven that the living environments (like community and school) are crucial for the relationship between obesity and objective social economic status [4,[7][8]. The same results may be found in other living environments for teens.…”
Section: Internal Mechanism: Obesity and Osesmentioning
confidence: 73%
See 3 more Smart Citations
“…The interaction effect also can be found in the developed country and developing country, Low SES is risk factor for obesity in the developed country but is protective factor in developing country [8]. The studies above have proven that the living environments (like community and school) are crucial for the relationship between obesity and objective social economic status [4,[7][8]. The same results may be found in other living environments for teens.…”
Section: Internal Mechanism: Obesity and Osesmentioning
confidence: 73%
“…OSES is usually assessed by the indicators like educational level, occupation and income. Obesity has been found to be negatively correlated with objective social economic status in a number of studies [4]. In a same school, teenagers with low-SES were more likely to be obese than those with high-SES.…”
Section: The Association Between Oses and Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies might also examine mesolevel mechanisms, such as neighborhood differences in built environments across countries (Gordon-Larsen et al, 2006) and differences in school policies regarding diet and activity. Furthermore, recent studies conducted in Europe (Luiggi et al, 2021) and the US (Kim et al, 2020) have shown interaction effects between meso-and individual/family-level SES and overweight and obesity among children and adolescents. For example, Kim et al (2020) showed that, in the US, living in a high SES neighborhood is protective against obesity among higher-income children, but not among low-income children.…”
Section: Directions For Future Researchmentioning
confidence: 99%